Targeted therapy of pulmonary arterial hypertension: updated recommendations from the Cologne Consensus Conference 2018 - Höper, Marius; Apitz, Christian; Grünig, Ekkehard; Halank, Michael; Ewert, Ralf; Kaemmerer, Harald; Kabitz, Hans-Joachim; Kähler, Christian; Klose, Hans; Leuchte, Hanno; Ulrich, Silvia; Olsson, Karen M.; et al. (International journal of cardiology, 2018)
In the summer of 2016, delegates from the German Respiratory Society, the German Society of Cardiology and the German Society of Pediatric Cardiology met in Cologne, Germany, to define consensus-based practice recommendations for the management of patients with pulmonary arterial hypertension (PAH). These recommendations were built on the 2015 European Pulmonary Hypertension guidelines and included new evidence, where available. The treatment algorithm for PAH was modified based on the observation that there are now many patients diagnosed with IPAH who are at an advanced age and have significant cardiopulmonary comorbidities. For patients newly diagnosed with classic forms of PAH, i.e. younger patients without significant cardiopulmonary comorbidities, the consensus-based recommendation was to use initial combination therapy as the standard approach. The use of monotherapies was no longer considered appropriate in such patients. The choice of treatment strategies should be based on the risk assessment as proposed in the European guidelines. In patients presenting with a low or intermediate risk, oral combination therapy with endothelin receptor antagonists and phosphodiesterase-5 inhibitors or soluble guanylate cyclase stimulators, respectively, should be used. In high-risk patients, triple combination therapy including a subcutaneous or intravenous prostacyclin analogue should be considered. For patients who suffer from PAH and significant cardiopulmonary comorbidities, initial monotherapy is recommended and the use of combination therapies should be considered on an individual basis. The latter recommendations are based on the scarcity of evidence supporting the use of combination therapy and the higher risk of drug-related adverse events in such patients.